Bio-electrocatalytic conversion of food waste to ethylene via succinic acid as the central intermediate - Pichler,CM; Bhattacharjee,S; Lam,E; Su,L; Collauto,A; Roessler,MM; Cobb,SJ; Badiani,VM; Rahaman,M; Reisner,E (ACS Catalysis, 2022)
Ethylene is an important feedstock in the chemical industry, but currently requires production from fossil resources. The electrocatalytic oxidative decarboxylation of succinic acid offers in principle an environmentally friendly route to generate ethylene. Here, a detailed investigation of the role of different carbon electrode materials and characteristics revealed that a flat electrode surface and high ordering of the carbon material are conducive for the reaction. A range of electrochemical and spectroscopic approaches such as Koutecky–Levich analysis, rotating ring-disk electrode (RRDE) studies, and Tafel analysis as well as quantum chemical calculations, electron paramagnetic resonance (EPR), and in situ infrared (IR) spectroscopy generated further insights into the mechanism of the overall process. A distinct reaction intermediate was detected, and the decarboxylation onset potential was determined to be 2.2–2.3 V versus the reversible hydrogen electrode (RHE). Following the mechanistic studies and electrode optimization, a two-step bio-electrochemical process was established for ethylene production using succinic acid sourced from food waste. The initial step of this integrated process involves microbial hydrolysis/fermentation of food waste into aqueous solutions containing succinic acid (0.3 M; 3.75 mmol per g bakery waste). The second step is the electro-oxidation of the obtained intermediate succinic acid to ethylene using a flow setup at room temperature, with a productivity of 0.4–1 μmol ethylene cmelectrode–2 h–1. This approach provides an alternative strategy to produce ethylene from food waste under ambient conditions using renewable energy.